PENGARUH PERSEPSI MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN (AMDK) PADA CV. MARASA AMERORO - Tauwi, Tauwi (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
This study aims to determine "The influence of brand perception, price and product quality on the Purchase Decision of Bottled Drinking Water (AMDK) at the CV. Marasa Ameroro. The population in this study is the consumer of bottled drinking water, Marasa Ameroro. The determination of the sample in this study is 10 x the number of variables, where the number of variables in this study there are 4 (four) variables, then: 10 x 4 = 40 respondents. The analytical tool used is multiple linear regression analysis. The results of this study indicate that brand perception, price and product quality simultaneously have a significant effect on purchasing decisions for bottled drinking water (AMDK) Marasa Ameroro. Brand perception partially has a positive and significant effect on purchasing decisions, price partially has a positive and significant effect on purchasing decisions, product quality partially has a positive and significant effect on purchasing decisions for bottled drinking water (AMDK) CV. Marasa Ameroro.